Survey on Prevalence, Risk Factors and Molecular Detection of Fasciola in Pakistan - Sarwar, Muhammad Muaz; Butt, Asif Ali; Ashfaq, Khurram; Chughtai, Sobia Amir; Javed, Sana; Zulfiqar, Saba; Majeed, Lubna; Javaid, Talha; Khan, Arsalan; Alvi, Mughees Aizaz (Indus Journal of Bioscience Research, 2025)
Fascioliasis is caused by the liver fluke Fasciola hepatica, poses significant threat to livestock and human health worldwide, particularly in Punjab, Pakistan. In this study, a comprehensive analysis of Fasciola hepatica infection was conducted in the livestock population of the Punjab region, focusing on the districts of Faisalabad, Lahore, and Bahawalpur. This study examined the liver and bile ducts of animals and collected live adult flukes for further analysis. Subsequently, DNA extraction was carried out and the cytochrome c oxidase subunit 1 gene of mitochondrial DNA was targeted using PCR amplification. The successful amplification of PCR products was confirmed through visualization on agarose gels. DNA sequencing was employed to characterize the Fasciola hepatica isolates. The findings of this study revealed that among the 1448 samples collected from buffalo, cattle, sheep, and goats, only 11.46% were infected with Fascioliasis. Buffalo exhibited the highest prevalence (14.16%), followed by cattle (12.81%), sheep (9.13%), and goats (8.12%). Among the breeds, Nilli-Ravi and H.F cross had the highest prevalence, while Khundi and Cholistani showed the lowest rates of infection. Fascioliasis was more common in females (14.52%) than in males (10.16%), with the 4-5 years age group having the highest prevalence (15.73%). This study provides crucial insights into the prevalence and distribution of Fascioliasis in the studied cattle population. Understanding the factors influencing infection rates can facilitate early detection and prompt treatment. However, further research is needed to develop effective control and prevention strategies for this significant livestock and public health concern in Punjab, Pakistan.